2016
DOI: 10.21037/tau.2016.02.04
|View full text |Cite
|
Sign up to set email alerts
|

Clinical applications of low-intensity pulsed ultrasound and its potential role in urology

Abstract: Low-intensity pulsed ultrasound (LIPUS) is a form of ultrasound that delivered at a much lower intensity (<3 W/cm2) than traditional ultrasound energy and output in the mode of pulse wave, and it is typically used for therapeutic purpose in rehabilitation medicine. LIPUS has minimal thermal effects due to its low intensity and pulsed output mode, and its non-thermal effects which is normally claimed to induce therapeutic changes in tissues attract most researchers’ attentions. LIPUS have been demonstrated to h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
93
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(93 citation statements)
references
References 68 publications
0
93
0
Order By: Relevance
“…On the horizon for the treatment of ED is low-intensity pulsed ultrasound (LIPUS), a non-invasive method of upregulating endogenous mesenchymal stem cells [71]. Studies have shown that LIPUS stimulates cell proliferation through activation of integrin receptors and the Rho/ROCK/Src/ERK signaling pathway [72], and by promoting the multilineage differentiation of mesenchymal stem/progenitor cell lines through the ROCK-Cot/Tpl2-MEK-ERK signaling pathway [73].…”
Section: On the Horizonmentioning
confidence: 99%
“…On the horizon for the treatment of ED is low-intensity pulsed ultrasound (LIPUS), a non-invasive method of upregulating endogenous mesenchymal stem cells [71]. Studies have shown that LIPUS stimulates cell proliferation through activation of integrin receptors and the Rho/ROCK/Src/ERK signaling pathway [72], and by promoting the multilineage differentiation of mesenchymal stem/progenitor cell lines through the ROCK-Cot/Tpl2-MEK-ERK signaling pathway [73].…”
Section: On the Horizonmentioning
confidence: 99%
“…LIPUS is a particular type of ultrasounds shown in Fig 1a, which generates at a frequency of 1-3 MHz and repeats at 1 kHz with a duty cycle of 20% to deliver a low-intensity pulsed wave [27]. It has been proven to be very safe for human use for many aspects of the medical applications, such as bone healing [28], inflammation inhibiting [29], soft-tissue regeneration [30], and the induction of cell-membrane porosity. LIPUS has also been proven to help division and proliferation in many types of cells, such as algal cell [39,40], stem/progenitor cell [37] and mammalian cell [38] and can also increase CHO cells growth and antibody production [35], increase cell permeability [39] and enhance gene delivery by using microbubble [36].…”
Section: Introductionmentioning
confidence: 99%
“…LIPUS was previously demonstrated to promote bone formation and accelerate bone maturation in cases of bone fracture (6,7), distraction osteogenesis (8) and delayed fracture union (9). LIPUS appears to act by affecting the biological mechanisms of cell proliferation, gene regulation and cell differentiation (10). Osteosarcoma is characterized by the production of malignant osteoid matrix and differentiation of mesenchymal osteoblasts (11).…”
Section: Introductionmentioning
confidence: 99%